SDN-Based Approach to Select Allocation Strategies in Heterogeneous Wireless Sensor Networks - Júnior, Francisco; Matos, Fernando (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2015: Anais do V Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2015)
Managing a wireless sensor network is not a trivial task. Due to its limitations, such as sensors equipped with low power batteries, it is essential to extend the lifetime of the network. This task becomes harder when dealing with heterogeneous wireless sensor networks, in which sensors have different physical characteristics, such as battery capacity and radio transmission range. This paper proposes a model to dynamically select a sensor allocation approach in order to choose a set of sensors to process an application request. This selection takes into account the application characteristics and the physical aspects of the sensors.